Ideologia na Educação Ambiental: estudo com educadores/educadoras de Educação Ambiental no contexto da Associação dos Municípios do Oeste do Paraná - AMOP - Koppe, Marise (2017)
This dissertation questions the development of Environmental Education in a perspective that considers Sustainable Rural Development (DRS). It is translated into the challenges and dispositions that involve the school curriculum in the dimensions of the totality components that involve Environmental Education. Among the central objectives there are three to be highlighted: to understand how educators who teach Environmental Education appropriate the epistemological and philosophical concepts of Environmental Education included in the Basic Curriculum of the AMOP (CBA); identify obstacles and challenges in the educational process with indicatives of how ideological aspects appropriate education as a maintenance of social order; contribute to the thinking about Sustainable Rural Development (DRS) presented in the Basic Curriculum of the Association of Municipalities of the West of Paraná (AMOP). Although this study was based on bibliographic subsidies and structuring elements of this school curriculum, this research is predominantly a case study. t brings a cut of the Environmental Education practice developed by 77 teachers in 26 schools of 06 municipalities of the micro-region of Marechal Cândido Rondon. For this, the study made possible a sampling of the interpretations and practices that are being developed in the municipal public schools, starting from the insertion and purposes of the theme of Environmental Education in the curriculum. The study highlights the predominance and selection of certain knowledge that are relevant to the understanding that curricula are driven by the dynamics of society, influenced by the Ideological State Apparatus (IEA). The analyzes draw on the categories that develop reflections in the field of dialectical thought, whether of Marxist origin or the perspective of critical postmodernity, founders in the way of building knowledge, values and social practices. It is also consolidated as an effort to think the sense that educators have as subjects in the possible implications of the lack of training for the pedagogical practice of Environmental Education and the very conditions of life. It encourages them to recognize themselves in the role they play and in their involvement in building sustainability for the western region of Paraná, as opposed to the logic of a development model that results in social exclusion.